Acetabular labrum and its tears. Issue 3 (1st June 2003) - Narvani, A A; Tsiridis, E; Tai, C C; Thomas, P
Abstract : Groin pain is a major cause of morbidity in athletes. Only in the last decade have acetabular labrum tears been recognised as a possible diagnosis. Awareness of this condition is important for appropriate management. The basic science and pathological and clinical features of acetabular labrum tears are reviewed, and diagnostic and treatment options are presented.